The Use of Multi-criteria Analysis in Selecting Water Treatment Units in Sadu Water Treatment Plant, Bandung District, West Java Province, Indonesia - Riana Ayu Kusumadewi; Indry Kemala Sani; Winarni Winarni (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2019)
Abstract: Increasing the number of residents and still not fulfilling the scope of drinking water services for resident of Bandung Regency, Tirta Raharja Regional Water Supply Company is developing in the field of drinking water supply. To improve community drinking water services in the Bandung Regency area, Tirta Raharja Water Supply Company plans to add a drinking water tratment plant with a capacity of 150 liters/second located in Sadu Village, Soreang District, Bandung Regency. In the planning of the Sadu WTP (Sdau Water Treatmnet Plant) was carried out several stages of planning, i.e. literature study, preliminary survey, data collection, alternative selection of treatment units using multi criteria analysis, and calculation of treatment unit dimensions. the parameters under review are those that exceed the standard of quality according to the Minister of Health Regulation No. 492 of 2010, i.e. turbidity, BOD, COD and fecal coliform. The selection of Sadu WTP units is based on parameters that exceed drinking water quality standards. There were two alternative proposed (Alternative I and Alternative II) in drinking water treatment, i.e. complete unit (Alternative I) consisting of intake; hydraulic coagulation; hydraulic flocculation; tube settler sedimentation; rapid sand filter; reservoir; disinfection; and sludge drying bed, and slow sand filter unit (Alternative II) consisting of intake, pre-sedimentation, slow sand filter, reservoir, disinfection, and sludge drying bed. The method to be used in determining the unit plan is multi-criteria analysis which refers to aspects based on Minister of Public Works Regulation No. 18/PRT/M/2007. Based on the results of the scoring obtained, the complete treatment unit has the highest score, i.e. 4.05, so the alternative treatment used in the Sadu WTP is the complete treatment unit (Alternative I).